(untitled) (Research, Society and Development, 2020)
The environmental licensing process is a guarantee of a safe environment for polluting activities. The present work analyzed Belém-PA environmental license files for the gas station segment in association with urban land use and the shallow free aquifer, these factors can compromise environmental quality and risks to the public health. For this purpose, there was carried out a bibliographic research, as well as a survey of information in databases of the municipal, state, federal registry and fire department. Besides, it was concluded that the number of licensed gas stations does not match the reality, where 130 projects were identified. It was found that 33 gas stations, or 25%, meet the necessary licenses and 97 gas stations, or 75%, have some pending issues, showing the need for greater attention to the environmental licensing process, as well as the need to regularize the enterprises with some pending in licensing, to have adequate management control over such activity. Bearing in mind that this is a potential activity that causes environmental damage, it is often located within the urban areas and under conditions of shallow groundwater can compromise the quality of soil and groundwater, with risk to human health.